2015
DOI: 10.11622/smedj.2015090
|View full text |Cite
|
Sign up to set email alerts
|

The clinical profile of patients with anorexia nervosa in Singapore: a follow‑up descriptive study

Abstract: INTRODUCTIONThe prevalence rate of anorexia nervosa is lower in Asia than in the West, although studies have found that it is on the rise in Asia. This study aims to present the clinical profile of patients presenting with anorexia nervosa in Singapore. METHODSThe present study used archival data from the Eating Disorder Programme registry of the Department of Psychiatry, Singapore General Hospital, Singapore. Patient records from 2003 to 2010 were collected and analysed. Presenting characteristics of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Another possible explanation for the over-representation of other ethnicities may be the lower stigma associated with consulting psychiatrists in Western culture, and thus, more individuals of Caucasian ethnicity may be willing to seek help at our centre. (23) Similar to previous studies, (24) we found consistent underrepresentation of Malay and Indian ethnicities in our sample. In a study of 50 individuals with eating disorders treated at another general hospital in Singapore between 1991 and 1996, the ethnic make-up of patients of Malay and Indian ethnicities was both low at 10%.…”
Section: Discussionsupporting
confidence: 91%
“…Another possible explanation for the over-representation of other ethnicities may be the lower stigma associated with consulting psychiatrists in Western culture, and thus, more individuals of Caucasian ethnicity may be willing to seek help at our centre. (23) Similar to previous studies, (24) we found consistent underrepresentation of Malay and Indian ethnicities in our sample. In a study of 50 individuals with eating disorders treated at another general hospital in Singapore between 1991 and 1996, the ethnic make-up of patients of Malay and Indian ethnicities was both low at 10%.…”
Section: Discussionsupporting
confidence: 91%
“…A local study of 271 patients with eating disorders identified that 28.4 percent suffer from related medical complications, the commonest of which are bradycardia, osteoporosis or osteopenia and hypokalaemia. 12 Patients with atypical AN are no less prone to these complications. 2 Early diagnosis and intervention expedite recovery and improves outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…occur which also indicate self-harm behaviour (Sansone et al, 2005). According to Kuek et al (2015) anorexic individuals are generally observed to have a depressive profile. In a research done by Westen and Harnden (2001) it was observed that patients with prominent anorexic symptoms are likely to fit in a constricted/over-controlled profile i.e.…”
Section: Neurobiological Processes and Behavioural Patterns In Anorexia Nervosamentioning
confidence: 99%